PENERAPAN ALGORITMA FLUX-CORRECTED TRANSPORT PADA SKEMA PENYELESAIAN METODE ELEMEN HINGGA TAYLOR-GALERKIN UNTUK PROBLEM DAM-BREAK - Dahana, Mada
Abstract : Dam-break phenomenon can be modelled numerically using shallow water governing equations. The shallow water governing equations are classified as hyperbolic partial differential equation. According to the accuracy, there are two kinds of scheme in nmmerical modelling; those are low order scheme and high order scheme. Low order/first order scheme is highly dsive and has a poor degree of accuracy. However, this scheme is also monotonic which means has a tendency not to oscillate. High order scheme has a higher degree of accuracy than the low order scheme. Uf fortunately, due to special charateristic of hyperbolic equation, such scheme produces non-realistic oscillations in the wake of discontinuities. Basically, Flux-Corrected Transport Algorithm constructs each transportive flux of both scheme, one chosen to guarantee results free of spurious numerical oscillations, and hence a highly diffi,sive first order accurate scheme, and the other chosen to yield formally high order accuracy. The high order fluxes are weighted as heavily as possible, subject to the constraint that the non-physical oscillations associated with the high order scheme are not re-introduced. The Taylor-Gale.rkin finite element method will be used as a based dicretization scheme for the low order scheme and high order scheme.